The necessity of teaching values in the era of globalization - Umar Bakri (Tamilis Synex: Multidimensional Collaboration, 2023)
In the current global era, the status of value education has become very central because its status is highly required to be able to provide meaning to every material subject to lead the Indonesian nation towards an advanced national civilization. This article aims to crystallize the concept of the importance of values education that educators need to know in the face of the conditions of global technological progress. This research uses the concept of desk research to demonstrate the urgency of the importance of values education. The results of the conceptual preparation show that the use of technology needs to be balanced with values education so that the values and character of the Indonesian nation remain intact and preserved. If the current value inculcation in education is not strengthened, it is not impossible that the Indonesian nation will gradually lose its identity and will not be able to maintain its national identity because it is easily influenced by global foreign culture. Therefore it can be concluded that technological progress needs to be enhanced through values education as a filter so that students can be critical in moral reasoning and considerations and be able to choose good and correct values on religious grounds. And morals, ethics and customs applied in Indonesia.